If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 = 4(x + 5) Reorder the terms: -2 + 3x = 4(x + 5) Reorder the terms: -2 + 3x = 4(5 + x) -2 + 3x = (5 * 4 + x * 4) -2 + 3x = (20 + 4x) Solving -2 + 3x = 20 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2 + 3x + -4x = 20 + 4x + -4x Combine like terms: 3x + -4x = -1x -2 + -1x = 20 + 4x + -4x Combine like terms: 4x + -4x = 0 -2 + -1x = 20 + 0 -2 + -1x = 20 Add '2' to each side of the equation. -2 + 2 + -1x = 20 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 20 + 2 -1x = 20 + 2 Combine like terms: 20 + 2 = 22 -1x = 22 Divide each side by '-1'. x = -22 Simplifying x = -22
| 6x+32=16x-8 | | 15y+5=5 | | 2x^2+19xy+24y^2=0 | | 16x^2-4x^4=0 | | 13x+32=16x-48 | | 15+x=1 | | 25x^2-1=10x | | BY=36 | | 7(x+7)=7x+49 | | 9x-(3/2)y=1 | | 1x+40=1x-10 | | (x^2+9)%(x-3) | | 12+3x^2+12x=0 | | b-c^2=5 | | 11x-13=8x+7 | | (4x^2-13x-5)%(x-2) | | h(x)=0.04x^2-3.5+100 | | 15a+5b=85 | | 4x+64x^2=0 | | 9b^2-Z=103 | | 7x^2-4x-2=0 | | -7(-1.75+-0.125y)-y=13 | | 4(3a+3)-(4a+6)=15 | | p=13-6 | | 12n+4(n+4)-4(n+1)= | | 12x=15-3x | | 24=-2c | | 48=-4h | | 1-49y^2=0 | | 7(4.4+0.2y)-4y=-7 | | r-6=-10 | | 2/(3(x^(4/3))) |